BLACK SOUTH AFRICANS’ PERCEPTIONS AND EXPERIENCES OF THE LEGAL CHILD ADOPTION ASSESSMENT PROCESS - Gerrand, Priscilla; Stevens, Garth (Social Work/Maatskaplike Werk, 2019)
Domestic adoption is usually considered to be in the best interests of abandoned children. However, although ongoing efforts have been made to recruit prospective black adopters, adoption rates remain low. A grounded theory study was conducted to explore how black South Africans perceive and experience the adoption assessment process regarding the adoption of abandoned children. Findings indicated that social workers regard a rigorous assessment process as essential to ensure that adoption applicants are fit and proper to adopt, whereas prospective adopters deem the process unreasonable. The grounded theory emerging addressed tensions around adoption policy and practice, and the perceptions and experiences of adoption.